Bile acids inhibit human purinergic receptor P2X4 in a heterologous expression system - Ilyaskin, Alexandr; Sure, Florian; Nesterov, Viatcheslav; Härteis, Silke; Korbmacher, Christoph (Journal of General Physiology, 2019)
We recently demonstrated that bile acids, especially tauro-deoxycholic acid (t-DCA), modify the function of the acid-sensing ion channel ASIC1a and other members of the epithelial sodium channel (ENaC)/degenerin (DEG) ion channel family. Surprisingly, ASIC1 shares a high degree of structural similarity with the purinergic receptor P2X4, a nonselective cation channel transiently activated by ATP. P2X4 is abundantly expressed in the apical membrane of bile duct epithelial cells and is therefore exposed to bile acids under physiological conditions. Here, we hypothesize that P2X4 may also be modulated by bile acids and investigate whether t-DCA and other common bile acids affect human P2X4 heterologously expressed in Xenopus laevis oocytes. We find that application of either t-DCA or unconjugated deoxycholic acid (DCA; 250 µM) causes a strong reduction (∼70%) of ATP-activated P2X4-mediated whole-cell currents. The inhibitory effect of 250 µM tauro-chenodeoxycholic acid is less pronounced (∼30%), and 250 µM chenodeoxycholic acid, cholic acid, or tauro-cholic acid did not significantly alter P2X4-mediated currents. t-DCA inhibits P2X4 in a concentration-dependent manner by reducing the efficacy of ATP without significantly changing its affinity. Single-channel patch-clamp recordings provide evidence that t-DCA inhibits P2X4 by stabilizing the channel's closed state. Using site-directed mutagenesis, we identifiy several amino acid residues within the transmembrane domains of P2X4 that are critically involved in mediating the inhibitory effect of t-DCA on P2X4. Importantly, a W46A mutation converts the inhibitory effect of t-DCA into a stimulatory effect. We conclude that t-DCA directly interacts with P2X4 and decreases ATP-activated P2X4 currents by stabilizing the closed conformation of the channel.
CRIS-Team Scopus Importer:2019-06-21